The Potential Therapeutic Use of Agarwood for Diabetes: A Scoping Review - Mohammad Adi Mohammad Fadzil; Norhashimah Abu Seman; Aswir Abd Rashed (MDPI AG, 2024)
Introduction: In 2019, 9.3% (463 million) of adults worldwide had diabetes, according to the International Diabetes Federation (IDF). By 2030, the number will rise to 10.2% (578 million) and 10.9% (700 million) by 2045 if effective prevention methods are not implemented. Agarwood is a pathological product and valuable plant due to its numerous medicinal properties, and it is used as an essential ingredient in medicine. Therefore, we conducted this review to determine agarwood's potential health benefit effect on type 2 diabetes. Results and Discussion: Although no clinical trials were found, the evidence from in vitro and in vivo studies is promising. Agarwood has shown the ability to reduce the activity of α-glucosidase, α-amylase, and lipase, promote adiponectin secretion during adipogenesis, and reduce oxidative stress. Animal studies elucidated hypoglycaemic, antidyslipidemia, anti-obesity, and organ protective effects from agarwood. Materials and Methods: Original articles were searched in three databases (PubMed, Scopus, and Cochrane Library) using the medical subject heading (MeSH) term "diabetes" crossed with the term "agarwood" from 2008 to 2024. Synonyms and relevant search terms were also searched. Conclusions: This effect underscores the need for further research and the potential for groundbreaking discoveries in the field of diabetes treatment.